Seleksi Individu M3 Berdasarkan Karakter Umur Genjah dan Produksi Tinggi pada Tanaman Kedelai (GlycinemaxL. Merrill) Individual Selection of M3 based on the character of time early ripening and high production soybean plant (Glycine max L. Merrill - Yoke Blandina Larasati Sihombing; Diana Sofia Hanafiah; Y Husni (Universitas Sumatera Utara, 2016)
The aim of the research was to obtain the selected M3generation soybean plant (Glycine max L Merril). The research was conducted on the experimental field of Faculty of Agriculture USU (± 25 m altitude) from AuGust 2015 until December 2015. The parameters observed wer: the time of flowering, the plant height, the number of primary branches, the time of harvest, the number of one seed pods, the number of two seed pods, the number of three seed pods , the number of four seed pods, the number of pods, the number of empty pods, the number of seed s of one seed pod, the number seeds of two seed pod, number of three seeds of three seed pod, the number of seeds of three seed pod, the number of seeds of four seed pod, s, the seed weight, the weight of 100 seeds.The result showed that the gamma irradiation at M3generation at 100 Gy, 200 Gy and 300 Gy affected the character the time of flowering, the time of harvets, the plant height, the number of productive branches, the number of pods, the number of seeds, the seed weigth, the weigth of 100 seeds. At 200 Gy the population number of productive plant increased and at 300 Gy showed the longer time of flowering. Key words : M3 generation,selection, soybean.